EFEITOS DE RETARDADORES DE CRESCIMENTO EM SOJA (Glycine max L. MERRILL) - Castro, Paulo R. C.; Homma, SÃ©rgio K.; Cato, Stella C. (REVISTA DE AGRICULTURA, 2016)
EFEITOS DE RETARDADORES DE CRESCIMENTO EM SOJA (Glycine max L. MERRILL)